The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.3748/wjg.15.1254
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of capsule endoscopy in patients diagnosed or suspected with esophageal varices

Abstract: AIM:To review the literature on capsule endoscopy (CE) for detecting esophageal varices using conventional esophagogastroduodenoscopy (EGD) as the standard. METHODS:A strict literature search of studies comparing the yield of CE and EGD in patients diagnosed or suspected as having esophageal varices was conducted by both computer search and manual search. Data were extracted to estimate the pooled diagnostic sensitivity and specificity. RESULTS:There were seven studies appropriate for meta-analysis in our stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 20 publications
0
20
1
4
Order By: Relevance
“…Also, as in the Choe et al [21] study, we found that concordance rates on grading esophageal varices were excellent at 95% (κ = 0.91). These results are better than those reported by using endoscopy capsule for detection of esophageal varices [7][8][9] . With regards to erosive esophagitis diagnosed at upper endoscopy, E.G.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Also, as in the Choe et al [21] study, we found that concordance rates on grading esophageal varices were excellent at 95% (κ = 0.91). These results are better than those reported by using endoscopy capsule for detection of esophageal varices [7][8][9] . With regards to erosive esophagitis diagnosed at upper endoscopy, E.G.…”
Section: Discussioncontrasting
confidence: 54%
“…Several studies have shown that ECE is safe and has an acceptable accuracy for the evaluation of esophageal varices and can be used as an alternative to EGD for the screening of portal hypertension, especially in patients unable or unwilling to undergo EGD [7,9] . Unsedated small-caliber transnasal esophagoscopy offers the possibility of efficient and accurate endoscopic assessment of the esophagus, with less cost and fewer risks compared with sedated upper endoscopy, and can be used as a method to screen for esophageal disease in a primary care population [11][12][13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of seven studies verified that CE has acceptable sensitivity and specificity (85.8% and 80.5%, respectively) in detecting esophageal varices [10,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis of seven studies involving 446 patients, ECE was found to have a sensitivity of 86 % and specificity 81 % in detecting esophageal varices (Fig. 2.12) [30].…”
Section: Indications For Ecementioning
confidence: 99%